2016
DOI: 10.1166/jbt.2016.1412
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surgical Approach for the Reconstruction of Critical-Size Mandibular Defects Using Calcium Sulphate/Hydroxyapatite Cement, BMP-7 and Mesenchymal Stem Cells-Histological Assessment

Abstract: A novel construct has been developed to induce bone formation within a pedicle muscle flap. A critical size defect (20 × 15 mm 2 ) was created in the mandible of ten rabbits. The masseter muscle was adapted to fill the surgical defect and a combination of calcium sulphate/hydroxyapatite cement (CERAMENT™lSPINE SUPPORT), BMP-7 and rabbits' mesenchymal stromal cells (rMSCs) was injected into the muscle tissue. Bone regeneration was evaluated 3 months after surgery. Limited areas of bone formation anatomically br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…Interestingly, bone thickening was also noticed on the host bone next to the grafted defect because of the stimulating effect of SCPC granule dissolution on host bone cell activity. The later observation was confirmed with our previous work [ 2 ]. Collectively, the findings of the analysis indicate that the DSM/SCPC/hBMSC tissue engineering scaffold can be used for bone augmentation and tissue regeneration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, bone thickening was also noticed on the host bone next to the grafted defect because of the stimulating effect of SCPC granule dissolution on host bone cell activity. The later observation was confirmed with our previous work [ 2 ]. Collectively, the findings of the analysis indicate that the DSM/SCPC/hBMSC tissue engineering scaffold can be used for bone augmentation and tissue regeneration.…”
Section: Discussionsupporting
confidence: 90%
“…But, they are involved with the possibility of extreme immune reaction, communication of infectious diseases and slower integration with native tissue. The advancement in tissue engineering by developing skeletal muscle grafts from homologous and autologous tissues has been lately suggested as a possible option for bone replacement [2][3][4][5]. The reasoning for the utilisation of local matrix materials is the separation of site-specific extracellular matrix and gives the matrix`s proteins impressions of the previous inhabitant cells.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this high reabsorption rate is the enhancement of pore formation and subsequent angiogenesis and bone ingrowth in vivo [ 31 ]. In addition, during bone regeneration, a variety of mechanisms have been proposed for the role of CS, including osteoconduction and/or osteoinduction [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nature of cell populations around and inside the PE disc was evaluated. On another hand quantitative data was obtained using histomorphometery to estimate the percentage of regenerated bone, residual cement (empty space), and fibrous/muscular tissue was estimated, following well established protocol [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inadequate vascularity, nutritional background, and tissue sustainability have always been the main difficulties in the reconstruction of critical bone defects in the head and neck region ( Pogrel et al, 1997 , Schliephake, 2009 ). Therefore, to address the problem of insufficient angiogenesis with engineered grafts, studies have suggested the use of skeletal muscle as a bioreactor to optimize bone regeneration and vasculature ( Heliotis et al, 2006 , Ayoub et al, 2007 , c2008 , Kokemueller et al, 2010 , Liu et al, 2011 ; Oryan et al, 2014 , Alfotawi et al, 2017 , Alfotawi et al, 2016 ). However, these promising results are also accompanied by some limitations, including donor site morbidity and inadequate graft availability.…”
Section: Introductionmentioning
confidence: 99%